The Trials and Tribulations of Informal Diversity Workers and How Leadership Can Help: A Qualitative Analysis - (:unkn) unknown (My University, 2023)
A crucial part of including diversity, equity, and inclusion within the workplace involves the efforts of diversity workers (Ahmed, 2017) who introduce equitable and inclusive measures, policies, rituals, and customs into the workplace. Informal diversity workers voluntarily or involuntarily conduct this unpaid labor within their organizations to enact inclusive and equitable measures. This dissertation analyzes informal diversity workers’ experiences and the unique communication challenges they encounter, how they overcome these challenges, and how leadership can aid them in DEI efforts.Informal diversity workers offer unique perspectives as company employees with insight into the organizational culture while conducting informal DEI procedures. This dissertation adopts an interpretive fieldwork method by interviewing 17 informal diversity workers from various organizations across the United States. Research questions include, What are the communicative challenges that informal diversity workers face when implementing DEI into organizations? How do informal diversity workers combat challenges when implementing DEI into organizations? How can organizational leaders communicate support and advocate for informal diversity workers? Findings illuminate unique challenges informal diversity workers experienced. Diversity workers struggled with conceptualizations of success and the ever-changing nature of success within DEI work. Second, White-identifying participants discussed diversity as racially bound, perpetuating essentialism and Whiteness. Diversity workers also described how their work was not taken seriously by organizational members and leadership. Lastly, this informal diversity work was described as emotionally taxing. Diversity workers overcame these challenges through self-preservation and building a community. Self-preservation was achieved by leaving the organization, accepting challenges as a part of their job, and justifying challenges. Diversity workers also discussed the importance building a community which allowed them to have a safe place with people who share similar values. Further, this study provides practical steps that organizational leaders can take to support informal diversity workers and enact DEI measures for sustainable change. Findings indicate that leaders can aid diversity workers by embedding DEI initiatives within the organization’s makeup through consistent communication, training, and hiring practices. Second, leaders can use their organizational power and employ communication strategies to collaborate with diversity workers to further DEI initiatives.
Keywords: DEI initatives; Diversity Equity and Inclusion; Diversity work; Inclusive Organization; Leadership; Organizational Communication